Gestión financiera de la Compañía de Transporte Atlas C.A. Cotacatran en la cuidad de Guayaquil en el periodo 2022 -2023. - Silva Cedeño, Estefanía Alejandra (2024)
During the completion of this case study on the financial management of the transportation company Atlas C.A. Cotacatrans interviewed the accountant in charge, Mr. Marlon Bernabé, who helped by providing us with information on the financial statements for the periods 2022-2023, where a horizontal analysis and profitability and solvency indicators were carried out to learn more. in depth the situation that the company was going through and what its economic development was like in these periods to be able to cover all its obligations. The primary objective of this research is an analysis of financial management within the transportation company, the aforementioned indicators being of great help. Therefore, for this case study we used the analytical-descriptive method that helped us interpret the information obtained through the implemented strategies, thus having a more understandable vision within this research on the financial management carried out. the company. Finally, with the help of all these instruments they allowed new measures to be implemented that help them improve the deficits that were obtained during the periods analyzed.